2023
DOI: 10.1039/d2ay01714h
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the electrophoretic separations on a surface-accessible and flexible fibre-based microfluidic devices

Abstract: Electrophoretic separation of charged ions on a textile-braided structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Textile-based electrofluidics is still in its infancy with the majority of studies being carried out on single yarn substrates [18,[30][31][32]. To date, there have been only limited reports on the application of more complex 3D textile structures [33][34][35]. Our research group recently reported the work on polyester braids as a 3D textile structure for electrofluidics [33].…”
Section: Introductionmentioning
confidence: 99%
“…Textile-based electrofluidics is still in its infancy with the majority of studies being carried out on single yarn substrates [18,[30][31][32]. To date, there have been only limited reports on the application of more complex 3D textile structures [33][34][35]. Our research group recently reported the work on polyester braids as a 3D textile structure for electrofluidics [33].…”
Section: Introductionmentioning
confidence: 99%
“…Textile-based electrofluidics possess many advantages opening new opportunities in biomedical research applications [1][2][3][4][5]. In textile-based electrofluidics, thousands of capillary channels between yarns of textile facilitate active fluid flow with the help of electric field, diminishing the limitations associated with passive flow [6].…”
Section: Introductionmentioning
confidence: 99%